Environmental influences on MNE subsidiary roles: economic integration and the Nordic countries - Benito, G R G; Grøgaard, B; Narula, R (Journal of International Business Studies, 2003)
We seek to examine the importance of environmental factors in determining MNE subsidiary roles. In particular, we examine the environmental factors associated with ‘deep’ integration schemes such as the EU. Such schemes require a convergence of economic structure, due to the establishment of common regional institutions, regulations and policies. Specifically, we distinguish between the scope of activities performed by subsidiaries, and the level of competence of those subsidiaries. The empirical analysis is based on a large-scale survey of foreign-owned units in Denmark, Finland and Norway. These Nordic countries differ with regard to their EU-membership status – Norway being the ‘outsider’, while the others are members – but are very similar to each other in most other respects. Our data show that subsidiaries in Norway report significantly lower scores for both scope of activities and levels of competence. The effects remain strong even when we are controlling for other potentially influential factors. The findings indicate that being on the ‘outside’ of the EU may indeed carry the price of becoming less attractive to MNE activity.